MATERIAL FLOW ANALYSIS OF WASTE BANK ACTIVITIES IN INDONESIA: CASE STUDY OF MEDAN CITY - Hafizhul Khair; Iga Yusmaidah Siregar; Indriyani Rachman; Toru Matsumoto (Universitas Trisakti, 2019)
Aims: This study aims to improve waste bank activities in Medan and make them more efficient Methodology and Results: The study involved the collection of secondary and primary data. The secondary data collected involved a general description of the study area, number, status, and location of the waste bank. Primary data included interviews and field research on selected waste banks. Importantly, survey and data collection were conducted from December 2017 to April 2018. A semi-structured interview survey approach was conducted to collect the data. Using the Material Flow Analysis (MFA) methodology, the findings of the study showed that of the total amount of the input material, 87.4 % is a recyclable waste and 12.6 % water. Also, the waste bank activities generate 87.2% recyclable items, 12.6% wastewater, and 0.2% residues. Conclusion, significance, and impact study: The findings are essential in understanding the use of resources to provide information for improving waste bank activities and waste management. Apart from the community, the government also plays a significant role in supporting the future of waste banks. This study found that waste bank activities are still conventional, with no technology adoption. In the future, the waste bank should be more efficient and manage large amounts of wastes, because the potential for recyclable products is still abundant.